The origin of William Richardson’s 1771 description of a Labrador Inuit snow house - Stopp, Marianne (Études/Inuit/Studies, 2013)
Researchers of Labrador Inuit history have long known of William Richardson’s brief account of his 1771 voyage to southern Labrador and his detailed description of a snow house. This research note compares this description to George Cartwright’s text on the same subject to show that Richardson’s information derives from Cartwright’s. Although Richardson correctly describes a snow house, it is nevertheless secondary information. The comparison also shows the importance of differentiating verifiable information from speculation or, in this case, replication and how easily an historical narrative can take on the appearance of a primary source.